"Na velhice também há vida" : os significados em torno da vida social dos velhos na cidade de Cuiabá - Silva, Thiago Oliveira da (2017)
This dissertation is about the meanings constructed among the social life of the elderly persons. This is an ethnographic study about a network of sociability, composed of men and women, at least, sexagenarians, belonging to the low and middle strata of the city of Cuiabá. The social representations, sociability, gender, the categories of family, human body, retirement and technology are issues presented in this study. It also discuss the approach of modern society, which characterize the elderly persons tied to stereotypes, according to them, the older age persons no longer have social roles. This study was carried out, based on the understanding that such stereotypes are socially constructed. The results indicated multifaceted and heterogeneous representations about the elderly persons. The meanings of their social life are constantly re-elaborated according to their life trajectories, indicating that any of these dimensions only makes sense when interpreted through the participants’ social reality.